2024
DOI: 10.3389/frdem.2024.1297193
|View full text |Cite
|
Sign up to set email alerts
|

Prior infections are associated with smaller hippocampal volume in older women

Vladimir A. Popov,
Svetlana Ukraintseva,
Hongzhe Duan
et al.

Abstract: Accumulating evidence suggests that infections may play a major role in Alzheimer's disease (AD), however, mechanism is unclear, as multiple pathways may be involved. One possibility is that infections could contribute to neurodegeneration directly by promoting neuronal death. We explored relationships between history of infections and brain hippocampal volume (HV), a major biomarker of neurodegeneration, in a subsample of the UK Biobank (UKB) participants. Infectious disease diagnoses were based on ICD10 code… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…Some studies also suggested that the aggregation of pTau may be induced by infections, among other factors ( Lee et al, 2022 ; Sathler et al, 2022 ; Shen et al, 2022 ; Tang et al, 2022 ). The involvement of infections in AD is an emerging field of AD research, and the literature on the factors that may influence both vulnerability to infections and neurodegeneration is increasing ( Yashin et al, 2018 ; Yong et al, 2021 ; Cairns, Itzhaki and Kaplan, 2022 ; Mancuso et al, 2022 ; Nuovo et al, 2022 ; Piekut et al, 2022 ; Sathler et al, 2022 ; Tang et al, 2022 ; Goldhardt et al, 2023 ; Ukraintseva et al, 2023 ; Popov et al, 2024 ). Nectin-2 (Nectin cell adhesion molecule 2) is a membrane component of adherens junctions that serves as an entry point for certain herpesviruses and may mediate response to the viral infection ( Ogawa et al, 2022 ; Goldhardt et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies also suggested that the aggregation of pTau may be induced by infections, among other factors ( Lee et al, 2022 ; Sathler et al, 2022 ; Shen et al, 2022 ; Tang et al, 2022 ). The involvement of infections in AD is an emerging field of AD research, and the literature on the factors that may influence both vulnerability to infections and neurodegeneration is increasing ( Yashin et al, 2018 ; Yong et al, 2021 ; Cairns, Itzhaki and Kaplan, 2022 ; Mancuso et al, 2022 ; Nuovo et al, 2022 ; Piekut et al, 2022 ; Sathler et al, 2022 ; Tang et al, 2022 ; Goldhardt et al, 2023 ; Ukraintseva et al, 2023 ; Popov et al, 2024 ). Nectin-2 (Nectin cell adhesion molecule 2) is a membrane component of adherens junctions that serves as an entry point for certain herpesviruses and may mediate response to the viral infection ( Ogawa et al, 2022 ; Goldhardt et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%